Nilai Karakter Bersahabat dalam Tradisi Barikan di Desa Wedusan untuk Siswa Sekolah Dasar - Farid Munfarida; Deka Setiawan; Muhammad Noor Ahsin (Journal Prakarsa Paedagogia, 2021)
This study aims to analyze the implementation of the Barikan Tradition in Wedusan Village, Dukuhseti District, Pati Regency and also the character values contained therein for the education of elementary school children. This research uses descriptive qualitative research methods. Data collection techniques used are observation, in-depth interviews and documentation or what is commonly known as data triangulation. The subjects studied were residents of the Barikan Tradition, community leaders and elementary school students of Wedusan Village. The Barikan tradition is a form of local wisdom that is still being carried out by future generations, in the implementation of this tradition it is carried out regularly in the afternoon before the evening of Friday Wage. The Barikan Tradition process is carried out for 1 day, starting from the preparation of the place, the offerings used, and when the traditional activity is carried out. The process of implementing this Barikan by using Islamic prayers and Javanese prayers. In the implementation of the tradition there are offerings or offerings that are used. As for the offerings used in this tradition, namely: golong rice, tala 'porridge, traditional snacks, bitter coffee, coconut. The friendly character value contained in the Barikan Tradition is also recognized and realized by the people of Wedusan Village. This was proven when the researchers conducted in-depth interviews with related parties.